Meningkatkan Antusiasme Siswa Kelas III Melalui Metode Window Shopping dalam Pelajaran IPAS: Penelitian - Alfika Wahyuni; Alif Mudiono; Mochammad Amirudin Ichda (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Students’ enthusiasm during classroom presentations is often a challenge, especially among third-grade elementary students who tend to lack confidence, be passive, and feel shy speaking in front of peers. This condition indicates that the learning process has not fully supported students’ courage and participation. This study aimed to examine the effectiveness of the window shopping method in improving the enthusiasm of third-grade students during presentations in IPAS learning and to describe its implementation. The study employed Classroom Action Research (CAR) with a descriptive quantitative approach, conducted in two cycles and one pre-cycle. The subjects were 19 third-grade students at SDN Blimbing 2 Malang in the even semester of the 2024/2025 academic year. The instruments used were enthusiasm observation sheets and documentation. The findings showed that the window shopping method contributed to increasing students’ enthusiasm, with the average score rising from 62 in the pre-cycle to 74 in cycle I and further to 85 in cycle II. The mastery level also improved from 42% to 84%. In conclusion, the window shopping method fosters an interactive learning atmosphere, enhances speaking confidence, promotes discussion involvement, and stimulates enthusiasm in IPAS learning.